New approaches to the organization of prestart preparation of qualified athletes in single combats (on an example of fencing) - Lopatenko, G. O.; Kosik, N. S.; Kosik, N. L. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to develop and investigate the effectiveness of complex extra-training means to enhance the prelaunch qualified athletes in fencing.